New insights into the 2012 Emilia (Italy) seismic sequence through advanced numerical modeling of ground deformation InSAR measurements. Issue 10 (26th May 2013) - Tizzani, P.; Castaldo, R.; Solaro, G.; Pepe, S.; Bonano, M.; Casu, F.; Manunta, M.; Manzo, M.; Pepe, A.; Samsonov, S.; Lanari, R.; Sansosti, E.
Abstract: [1] We provide new insights into the two main seismic events that occurred in 2012 in the Emilia region, Italy. We extend the results from previous studies based on analytical inversion modeling of GPS and RADARSAT‐1 InSAR measurements by exploiting RADARSAT‐2 data. Moreover, we benefit from the available large amount of geological and geophysical information through finite element method (FEM) modeling implemented in a structural‐mechanical context to investigate the impact of known buried structures on the modulation of the ground deformation field. We find that the displacement pattern associated with the 20 May event is consistent with the activation of a single fault segment of the inner Ferrara thrust, in good agreement with the analytical solution. In contrast, the interpretation of the 29 May episode requires the activation of three different fault segments and a block roto‐translation of the Mirandola anticline. The proposed FEM‐based methodology is applicable to other seismic areas where the complexity of buried structures is known and plays a fundamental role in the modulation of the associated surface deformation pattern. Key Points: Detection of active seismogenic structures responsible for ground deformation Evaluate the role of tectonic constrain on the modulation of ground deformation Provide a detailed characterization of the rock failure mechanisms